Using Semi-Analytic Technique for Solving Lane Emden Equations - Tawfiq, Luma; Hussein, Reem (Iraqi Journal of Science, 2023)
This paper propose the semi - analytic technique using two point osculatory interpolation to construct polynomial solution for solving some well-known classes of Lane-Emden type equations which are linear ordinary differential equations, and disusse the behavior of the solution in the neighborhood of the singular points along with its numerical approximation. Many examples are presented to demonstrate the applicability and efficiency of the methods. Finally , we discuss behavior of the solution in the neighborhood of the singularity point which appears to perform satisfactorily for singular problems.